Pengaruh Model Pembelajaran Cooperative Learning Terhadap Hasil Belajar Siswa Dalam Mata Pelajaran IPS Kelas V SDN 104204 Sambirejo Timur - Desy Amelia; Ibrahim Gultom (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This study aims to find out how the learning outcomes of students taught using the Teams Games Tournament (TGT) Cooperative Learning Model and the Student Team Achievement Division (STAD) Cooperative Learning Model. The type of research used is Quasy Experiment Design research. Based on the research that was conducted in class V SDN 104204 Sambirejo Timur, it showed that there were differences in student learning outcomes. It can be seen in the average learning outcomes in the experimental class 1 (TGT) obtaining an average score of 81.25, while in experimental class 2 (STAD) obtained an average value of 79. At the significance level produced in the t-test shows a result of 0.00 < than 0.05. Thus the results were obtained, namely the learning outcomes of students who were taught using the Teams Games Tournament (TGT) Cooperative Learning Model were higher than the learning outcomes of students who were taught using the Student Team Achievement Division (STAD) Cooperative Learning Model.